IMPLEMENTASI PEMBELAJARAN BLENDED LEARNNG PADA MATA PEAJARAN PA DI MASA PANDEMI COVID-19 DI SMA NEGERI 5 MALANG - Putri Fanditya Dwiningtyas; Abd Jalil; Nur Hasan (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
At the beginning of 2020, there was an uproar with the emergence of the COVID-19pandemic which spread to almost all corners of the world. This outbreak originated inWuhan, China. Due to the Covid-19 outbreak, Indonesia cannot carry out normallearning or learning as usual, it is required to maintain social distance and followhealth protocols. With the Covid-19 outbreak, learning cannot be maximized, with theholding of combined learning (Blended Learning), the learning process can be better.Blended learning is a combination of online learning and face-to-face learning. In thisblended learning, researchers conducted research in SMA Negeri 5 Malang by usingdescriptive qualitative research method with the type of case study research. Theresults showed that the implementation of blended learning in Islamic religiouseducation subjects during the covid-19 pandemic at SMA Negeri 5 Malang, whichincluded 3 aspects, namely planning which included designing learning programtargets, planning learning support offices and foundation, getting ready learningtimetables, and mingling. Then the execution of mixed learning incorporates onlinelearning and face-to-face learning and finally evaluation of blended learning, as wellas inhibiting and supporting factors in the implementation of blended learning.